The association between 2017 American College of Cardiology/American Heart Association guideline for hypertension and neonatal outcomes in Kenya: a retrospective study - Mami Hitachi; Kazuchiyo Miyamichi; Sumihisa Honda; Violet Wanjihia; Samson Muuo Nzou; Satoshi Kaneko (Tropical Medicine and Health)
Abstract Background Hypertension in pregnancy serves to screen for adverse perinatal outcomes. In 2017, the American College of Cardiology and American Heart Association recommended a new blood pressure category with lower hypertension thresholds, excluding pregnancy. This study aimed to explore the association between the 2017 redefined blood pressure categories in pregnancy and neonatal outcomes such as preterm birth and low birth weight. Methods This retrospective study used electronic records of the Maternal and Child Health Handbook registered by the Women and Infant Registration System. All women who had at least one antenatal care visit and delivery between January 2017 and April 2020 and between May and December 2022 were included in the study. A birth of less than 37 weeks was defined as preterm delivery. LBW was identified based on a newborn’s birthweight of less than 2500 g. The maximum blood pressure across all antenatal care visits was classified based on the newly recommended criteria. A generalized linear model with binomial distribution and logit link function was used to evaluate the association between new blood pressure categories and neonatal outcomes at different levels of health facilities. Results We analyzed data from 825 women. Of these, the prevalence was 13.7% for elevated blood pressure, 15.2% for stage 1 hypertension, 4.5% for non-severe stage 2 hypertension and 1.2% for severe stage 2 hypertension. For lower-level facilities, no significant associations were identified between the redefined blood pressure category and preterm birth or low birthweight. At higher-level facilities, preterm birth was only significantly associated with severe stage 2 hypertension (adjusted odds ratio:10.94; 95% confidence interval:1.08–110.93; P = 0.04) and low birthweight showed no association with the redefined category. Conclusion This study revealed no association between redefined lower blood pressure threshold and preterm birth and low birthweight in under-resourced settings. However, previous studies in well-resourced countries with larger sample sizes also reported a significant association. Therefore, further investigations are required.